COVID-19 Pandemic: Public Health Implications in Nepal - Asim, Mohammad; Sathian, Brijesh; van Teijlingen, Edwin; Mekkodathil, Ahammed; Subramanya, Supram Hosuru; Simkhada, Padam (Nepal Journal of Epidemiology, 2020)
Over the past few decades, we have seen several outbreaks of zoonotic coronavirus infections. These viruses have the potential of interspecies transmission leading to pathogenesis in humans. This particular respiratory coronavirus initially named 2019-nCOV, is known as severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). In the current situation, abiding to the general health guidelines is utmost important to maintain stronger immunity for fighting infections and protection from other environmental hazards.